Implementation of rehabilitation sanctions for victims of narcotics abuse for the sake of legal certainty - Ryan Adhi Pradana; Hartana Hartana; Nyoman Tio Rae (Journal of Law Science, 2024)
Drug abuse poses a serious global threat, including in Indonesia. To address this issue, the implementation of rehabilitation sanctions as an alternative to imprisonment has been introduced by law. However, despite aiming to protect and aid victims of drug abuse, the application of rehabilitation sanctions faces significant challenges regarding legal certainty. Research, using a normative legal approach and content analysis of narcotics and rehabilitation regulations, along with a study of court decisions related to rehabilitation sanctions, reveals fundamental issues. One key finding is the inconsistency in defining drug abuse victims, impacting the understanding and implementation of rehabilitation sanctions. Moreover, the term "may" in the law creates ambiguity concerning judges' obligations to impose rehabilitation sanctions. Practical constraints, like limited rehabilitation facilities and inadequate understanding of rehabilitation approaches among law enforcement, also affect effectiveness. Addressing these issues requires clarifying definitions, enhancing law enforcement's understanding through training, and improving rehabilitation facilities. The goal is to provide comprehensive protection and optimal recovery for those affected by drug abuse, ultimately benefiting Indonesia's criminal justice and rehabilitation systems.